Testes e provas: possibilidades de interrogar o "distúrbio articulatório" como categoria nosográfica na clínica de linguagem - Marchiori, Milena Quinto (2009)
This study focuses on a specific kind of symptomatic speech occurrence widely known as articulatory disorders as points relative to the used in the clinical speechlanguage pathologists descriptive the instrument apllied in the clinical field of speech therapy. In order to discuss this issue, recent literature in speech-language pathologists was discussed, followed by a retrospective analysis of the projects Language, Acquisition, and Language Pathology The manner through which instrumentation based on different theoretical perspectives leads to unique ways of leading the patient to the clinic was also discussed. To assess the clinical issues in this dissertation, two children were submitted to a stimulability test and, after the test, their speech was evaluated in a dialogue situation. This movement allowed me to observe that tests hinder speech and fade the speaker. After discussing the clinical material, I specially pointed out the importance of a linguistic reflection which would not operate stratification of speech in levels and systems, nor fade the speaker and the function of speech. I was thus able to establish a differentiated analysis of speech in these children and apprehend in discursive situations, singular movements which fade in directed/directioned activities. Finally, I problematized the nosographic categories through which language clinics operate and pointed towards the need to discuss them under a structural point of view thought. The reflections throughout this dissertation are theoretically based on the fundaments that guide the CNPq sponsored project Language, Acquisition, and Language Pathology, supervised by Profa. Dra. Maria Francisca Lier-DeVitto and by Profa. Dra. Lucia Arantes, (at the LAEL/PUC-SP). In this perspective, speech and the subject are intertwined, and the relation which the subject maintains with his or her own speech and the other s speech is articulated by linguistic functions; in essence, it is a commitment with the significant density of speech which does not fade the speaker